Acromegaloid facial appearance (AFA) syndrome: report of a second family. Issue 6 (June 1992) - Dallapiccola, B; Zelante, L; Accadia, L; Mingarelli, R
Abstract : A family is reported in which the 'acromegaloid facial appearance' (AFA) phenotype was segregating through two generations. The five affected persons showed a striking resemblance to the patients previously reported, including progressively coarse acromegaloid-like facial appearance, narrow palpebral fissures, bulbous nose, and thickening of the lips and intraoral mucosa, resulting in exaggerated rugae and frenula. These patients also had increased birth weight and dull mentality. It is unclear if the differences between the two families mark distinct syndromes or simply extend the AFA phenotype.